Adefovir treatment for chronic hepatitis B in heart transplant recipients. (21st March 2013) - Durante‐Mangoni, Emanuele; Iossa, Domenico; Pinto, Daniela; Molaro, Rosa; Agrusta, Federica; Amarelli, Cristiano; Ragone, Enrico; Grimaldi, Maria; Maiello, Ciro; Utili, Riccardo
Abstract Chronic hepatitis B is prevalent in the transplant setting and may cause significant complications. Effective control of viral replication is needed. Besides lamivudine, very little data are available on safety and efficacy of other drugs. We describe our experience with adefovir dipivoxil (ADV) in eight heart transplant recipients. Studies included a baseline liver biopsy, thrice‐monthly clinical, biochemical, and virological evaluations, including genotyping and viral load, polymerase gene sequencing for resistance mutations, liver and kidney function tests, and liver ultrasound. Of eight patients, six had fibrosis score ≤2 and negative HBeAg and seven had hepatitis B virus (HBV) genotype D. Upon ADV start, median HBV‐DNA was 5.8 logs IU/mL and alanine aminotransferase (ALT) levels were mostly normal. All patients had prior mild‐to‐moderate renal functional impairment. Seven of eight patients started ADV after a previous course of lamivudine. Five of these seven patients became HBV‐DNA undetectable within eight months. One patient with low baseline viremia started ADV de novo and suppressed HBV‐DNA. Median treatment duration was 66 months. ADV daily dose was halved in one patient due to renal function worsening. No ALT flares, hypophosphatemia, liver decompensation, liver cancer, or emergence of resistance was observed. Our data suggest that ADV may be a safe and effective rescue treatment for heart transplant recipients with lamivudine‐resistant chronic hepatitis B.